About responsibility - Flores Morales, Jorge (2015)
Responsibility is a value that consists of assuming the consequences of one’s acts. Obviously, man is the only being who possesses it because of its rationality. As such, it can develop this value avoiding unjustified excuses because there are evidences of a mistake in the process of realizing an assigned aim. In this context, several levels of responsibility exist, such as moral, personal, social, ecological, etc. On the other hand, an education in responsibility is a task that the educational system has to face in order to have a better constituted society, in front of new, contemporary challenges.